Improving the Company's Activities in the Field of Consulting Services in the International Market - Jinsi Wang; Denis Paleev (Communications of International Proceedings, 2021)
Credit consulting is a new type of business that is actively spreading today. Taking into account the growing interest of clients in funds attracted from outside for business development, an objective need arose for the development of such a type of services as credit counseling. Along with this, the offer of various credit programs by banks is also growing. Each of them not only offers the client special conditions, but also requires him to provide a completely specific set of documents and guarantees. It is becoming more and more difficult for a potential recipient of a loan to navigate on their own in this area and it is becoming easier to get lost in this flow. As the number of companies providing consulting services grows, competition between them intensifies, which requires management to find ways to increase competitive advantages.
Keywords: Consulting; consulting company; consulting services; credit; bank; competition; innovation; digital consulting.